Perceptions of Intra-Uterine Device Users in Mirebalais, Haiti: A Mixed Methods Study - Marie Boller; Meredith Jean-Baptiste; Christophe Millien; Theophile Renise; Marisa Nádas (Ubiquity Press, 2018)
Introduction: IUDs are safe, effective, and used worldwide to prevent unintended pregnancy. However, uptake in Haiti is low. There are limited data on IUD choice and experience in low resource settings; anecdotal reports from providers in Haiti have suggested that Haitian women are unlikely to choose to use or be satisfied with the IUD. The objective of this study is to explore the perceptions of a cohort of IUD users in Mirebalais, Haiti. Methods: In June and July 2015, an IRB-approved mixed methods study of women over age eighteen with hormonal or copper IUDs inserted at Hôpital Universitaire de Mirebalais (HUM) was performed in Mirebalais, Haiti. Results: Twenty-one eligible women participated, out of 58 women identified as eligible. Most women (81%) reported using the copper IUD; most (86%) had used the IUD for 6 months or more. Over half were under 30 years old (62%) and most had completed primary school or less (76%). Almost all (91%) reported prior pregnancies; 65% did not desire more children. The majority of participants were satisfied with the IUD, with 70% being very satisfied and 25% somewhat satisfied. Most women (71%) reported no very bothersome side effects, and would recommend the IUD to others (86%). Qualitative data highlighted positive perceptions of the IUD among users, as well as misperceptions and lack of knowledge regarding the IUD among members of their communities. Conclusion/Implications: Understanding of culture-specific perceptions is critical in addressing barriers to IUD uptake. Our findings indicate that IUDs can be an acceptable contraceptive method for women in Haiti, and suggest the possibility that increased access to the IUD may lead to increased acceptance of this method.